2011
DOI: 10.1152/jn.00136.2011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological identification and infralimbic responsiveness of rat intercalated amygdala neurons

Abstract: Intercalated (ITC) amygdala neurons are thought to play a critical role in the extinction of conditioned fear. However, several factors hinder progress in studying ITC contributions to extinction. First, although extinction is usually studied in rats and mice, most ITC investigations were performed in guinea pigs or cats. Thus it is unclear whether their connectivity is similar across species. Second, we lack criteria to identify ITC cells on the basis of their discharge pattern. As a result, key predictions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 56 publications
(77 reference statements)
8
89
0
Order By: Relevance
“…Importantly, we found that IL is necessary for forming a memory of extinction of avoidance, consistent with its role in extinction of fear conditioning (Burgos-Robles et al, 2007;Laurent and Westbrook, 2009b;Amir et al, 2011;Fontanez-Nuin et al, 2011;Sierra-Mercado et al, 2011). Previous studies have linked extinction of active avoidance with the amygdala (Jiao et al, 2011), medial septum (Pang et al, 2011), and anterior thalamus (Gabriel et al, 1983), but not to IL.…”
Section: Infralimbic Cortex Is Necessary For Avoidance Extinction Butsupporting
confidence: 84%
See 2 more Smart Citations
“…Importantly, we found that IL is necessary for forming a memory of extinction of avoidance, consistent with its role in extinction of fear conditioning (Burgos-Robles et al, 2007;Laurent and Westbrook, 2009b;Amir et al, 2011;Fontanez-Nuin et al, 2011;Sierra-Mercado et al, 2011). Previous studies have linked extinction of active avoidance with the amygdala (Jiao et al, 2011), medial septum (Pang et al, 2011), and anterior thalamus (Gabriel et al, 1983), but not to IL.…”
Section: Infralimbic Cortex Is Necessary For Avoidance Extinction Butsupporting
confidence: 84%
“…Previous studies have linked IL to fear extinction (Mueller et al, 2010;Peters et al, 2010;Santini and Porter, 2010;Thompson et al, 2010;Fontanez-Nuin et al, 2011;Holmes et al, 2012), proposing that IL inhibits freezing via feed-forward inhibition of the amygdala (Quirk et al, 2003;Amano et al, 2010;Amir et al, 2011). In particular, inactivating IL immediately before fear extinction training leaves extinction intact but impairs retrieval of extinction the next day (Laurent and Westbrook, 2009b;Sierra-Mercado et al, 2011;Holmes et al, 2012).…”
Section: Inactivation Of Il Impairs Extinction Of Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus modulates fear behavior by direct connections to the amygdala or indirectly via activation of the prefrontal cortex (Maren, 2005). Interestingly, the infralimbic region of the prefrontal cortex activates inhibitory intercalated neurons (Amir et al, 2011;Pinard et al, 2012), a population of neurons that were activated in our experiments by shortterm fasting and consequently reduced CEm activation by feed-forward inhibition (Supplementary Figure 8).…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, stimulation of the IL at the CS onset (Milad and Quirk, 2002), but not prior or after the CS (VidalGonzalez et al, 2006) has been shown to result in extinction of fear memory, suggesting its role in the gating of downstream structures involved in fear memory. The IL is thought to inhibit the amygdala, especially its basolateral complex (BLA) (Grace and Rosenkranz, 2002), and the effect of the IL on suppression of the BLA is mediated by inhibitory interneurons (Amir et al, 2011;Pare and Smith, 1993).…”
Section: Discussionmentioning
confidence: 99%